Ketahanan UMKM di Wilayah Rawan Banjir: Analisis Strategi Berbasis PESTEL di Kabupaten Kampar - Hayatul Khairul Rahmat; Rahmad Akbar; Nurkholis Nurkholis; Dzulhijjah Yetti; Muhammad Firjatullah Nur Akbar; Siti Masrohatin (Trends in Applied Sciences, Social Science, and Education, 2026)
This study aims to analyze the resilience of Micro, Small, and Medium Enterprises (MSMEs) in flood-prone areas in Kampar Regency using the PESTEL approach (Political, Economic, Social, Technological, Environmental, Legal). This research employs a qualitative approach with a case study design, utilizing data collection techniques such as in-depth interviews, field observations, and documentation involving MSME actors and relevant stakeholders. Data analysis was conducted thematically and mapped into the PESTEL framework to identify external factors influencing business resilience. The findings reveal that economic and environmental factors are the primary determinants affecting MSME vulnerability, particularly in terms of cash flow disruptions, asset damage, and recurring flood risks. Meanwhile, social and technological factors act as resilience enhancers through community networks and the adoption of digitalization. On the other hand, political and legal factors have not been optimal in supporting MSME resilience due to the lack of integrated policies and low levels of business legality. Based on these findings, this study formulates three main strategies to strengthen MSME resilience: adaptive, protective, and collaborative strategies. Adaptive strategies focus on business flexibility, protective strategies emphasize risk mitigation, and collaborative strategies highlight stakeholder synergy. This study contributes to the development of disaster-based MSME resilience studies and serves as a foundation for formulating disaster-resilient MSME policies at the regional level.